Young Citizens, Social Media, and the Dynamics of Political Learning in the U.S. Presidential Primary Election. (July 2018) - Edgerly, Stephanie; Thorson, Kjerstin; Wells, Chris
This study explores political learning among young adults during the 2016 U.S. presidential primary elections. We are interested in how the rise of digital and social media is affecting the ways young adults learn about political events as they happen. Using a rolling cross-section survey design, we surveyed a unique sample of American young adults every day for a period of 3 weeks. This method allows us to ask participants about breaking news events as they occur, and to connect knowledge of current events to self-report of media use during a very short time period. We examine the relationship between media exposure and political learning using both self-report media exposure measures and measures of the volume of attention to political events in the news media and via social sharing of news on Facebook. Results suggest that social media volume, not self-reports of exposure, was key in providing young adults with the opportunities to learn about politics during the 2016 U.S. primary season.